Sensitivity of human laryngeal squamous cell carcinoma Hep-2 to metrotexate chemoterapy - Galbiatti, A.L.S.; Caldas, H.C.; Padovani Junior, J.A.; Pavarino, E.C.; Goloni-Bertollo, E.M. (Experimental Oncology, 2012)
Aim: Methotrexate (MTX) is an antifolate agent that acts inhibiting purine and pyrimidine synthesis. The objective of the study was to evaluate the viability of Hep-2 human laryngeal cancer cells to the treatment with MTX chemotherapy in vitro. Methods: Cultured Hep-2 cells were treated with 0.25, 25.0 and 75 μM MTX for 24 h, and their viability was evaluated with Bcl-2-FITC antibody in flow cytometry. Results: The numbers of viable Hep-2 cells after 24 h treatment with 0.25, 25.0 and 75.0 uM MTX were 85.43%, 22.46% and 8.42%, respectively (p < 0.05). Therefore, MTX possesses a dose-dependent effect on viability of Hep-2 cells in vitro. Conclusion: The highest MTX concentration is associated with highest tumor cell sensitivity of human laryngeal cancer cells of Hep-2 line.